European Stroke Organisation expedited recommendation for the use of short-term dual antiplatelet therapy early after minor stroke and high-risk TIA. (June 2021) - Dawson, Jesse; Merwick, Áine; Webb, Alastair; Dennis, Martin; Ferrari, Julia; Fonseca, Ana Catarina; ,
Prevention of early recurrent ischaemic stroke remains a priority in people with TIA or ischaemic stroke. A number of trials have recently been completed assessing the efficacy of short-term dual antiplatelet therapy (DAPT) versus single antiplatelet therapy early after minor or moderate stroke or high-risk TIA. We present an Expedited Recommendation for use of dual antiplatelet therapy early after ischaemic stroke and TIA on behalf of the ESO Guideline Board. We make a strong recommendation based on high quality of evidence for use of 21-days of dual antiplatelet therapy with aspirin and clopidogrel in people with a non-cardioembolic minor ischaemic stroke or high-risk TIA in the past 24 hours. We make a weak recommendation based on moderate quality evidence for 30-days of dual antiplatelet therapy with aspirin and ticagrelor in people with non-cardioembolic mild to moderate ischaemic stroke or high-risk TIA in the past 24 hours.